A Novel Metal-Organic Framework Composite, MIL-101(Cr)@MIP, as an Efficient Sorbent in Solid-Phase Extraction Coupling with HPLC for Tribenuron-Methyl Determination. (2nd June 2019) - Zheng, Xinyuan; Wang, Junping
Abstract : A highly efficient and selective method based on core–shell molecularly imprinted polymers (MIL@MIP) and high performance liquid chromatography (HPLC) was developed and firstly used for the trace analysis of tribenuron-methyl (TBM) in complicated matrices. The MIL@MIP was prepared by surface molecular-imprinting technique, specially using MIL-101 as core, TBM as template molecule, methacrylic acid (MAA) as functional monomer, ethylene glycol dimethacrylate (EGDMA) as cross-linker, and azobisisobutyronitrile (AIBN) as initiator. The resulting MIL@MIP showed high affinity, recognition specificity, fast mass transfer rate, and efficient adsorption performance towards TBM with the adsorption capacity reaching up to 3.217 mg/g. It also showed high cross-selectivity for TBM among its six kinds of chemical structure analogues. Furthermore, using the MIL@MIP as solid-phase extraction (SPE) materials, the recoveries of TBM determined by HPLC were 84.6-92.3%, 93.3-106.7%, and 88.9-93.3% in the spiked river water, soil, and soybean samples, respectively, with the limit of detection of 0.3 ng/L, 1.5 ng/kg, and 1.5 ng/kg, accordingly. It was proved that the developed HPLC-MISPE method was fast, accurate, and sensitive for detecting the trace TBM in river water, soil, and soybean samples.